Rock Music and The Political Scripting of Vietnam War: Reading Dispatches by Michael Herr - Lalit Kumar (IAFOR Journal of Arts & Humanities)
Projections regarding the Vietnam War were articulated through various forms of representation. In 1960s America, a countercultural movement centered on country-folk music emerged and thrived as an alternative to mainstream nationalist music. Folk music evolved into folk-rock and ultimately into “rock and roll,” carrying distinct political and psychological messages that resonated with the collective conscience through diverse narratives and personas. The Vietnam War significantly influenced music production across genres, including the adoption of rock music by South Vietnamese bands, as observed by David James. The music industry played a pivotal role in reinforcing anti-war sentiments in the United States, exemplified by songs such as Buffy Sainte-Marie’s “Universal Soldier” and Phil Ochs’ “Vietnam Talking Blues.” Michael Herr’s Dispatches (1977), based on his tenure as a war correspondent for Esquire (1967–1969), underscores the integral role of music in shaping the cultural montage of the war. Herr’s narrative incorporates numerous musical references, providing a vivid and unrelenting portrayal of the war experience. This study explores the cultural interplay between music and literature during the Vietnam War, examining the implications of conceptualizing the conflict as a “mass media montage.” Using Herr’s Dispatches as a case study, it investigates how rock music encapsulates the war’s ambiguous energy, blurring the boundaries between artistic expression and the realities of conflict. The analysis considers the artistic, ideological, and cultural dimensions of the music produced and disseminated during the war, while also reflecting on how the lyrics referenced in Herr’s work reveal the psychological state of soldiers and the growing significance of counter-cultural music as the war progressed.